Cities after socialism: urban and regional change and conflict in post-socialist societies - Andrusz, Gregory D. (Blackwell, 1996)
Lit.
Literaturverz. S. [318] - 335
Keywords: Aufsatzsammlung; Stadtentwicklung; Verstädterung; Stadtplanung; Demokratisierung; Osteuropa; Sozioökonomischer Wandel; Transformationsländer; Kommunalpolitik